First record of the Zigzag elm sawfly Aproceros leucopoda (Hymenoptera: Argidae) in Greece - Tsikas, Angelos; Karanikola, Paraskevi (ENTOMOLOGIA HELLENICA, 2024)
The Zigzag elm sawfly Aproceros leucopoda Takeuchi, 1939 (Hymenoptera, Argidae) is a defoliator of elm trees of Asian origin recently introduced into Europe. In this publication, A. leucopoda is recorded in Greece from Xanthi, constituting the first record of this alien species to the country. The presented locality is the southernmost point of its hitherto known distribution in Europe.